Unlocking stories: older women’s experiences of intimate partner violence told through creative expression - McGarry, Julie; Bowden, Dawn (Wiley, 2017)
INTRODUCTION Intimate partner violence (IPV) exerts a detrimental impact on the lives and health of all who experience abuse. This includes both physical and mental health and wellbeing. The experiences of older women however may be different and these differences may not be recognised or accounted for within existing care provision. AIM To explore the impact of IPV on the lives and health of older women told from the particular perspective of older women themselves as these accounts are largely absence from existing IPV discourse. METHOD An arts based research approach with five older women survivors of IPV through the co-development and organisation of an arts based workshop. The workshop essentially encompassed four main arts strands and included the creation of clay models and poetry. FINDINGS The findings of the study highlight the significant impact of IPV on the lives, mental health and wellbeing of older women. This included feelings of social isolation, inability to trust others and a loss of self-identity.